Body weight in systemic lupus erythematosus is associated with disease activity and the adaptive immune system, independent of type I IFN - Teruya, Hiroyuki; Shoda, Hirofumi; Itamiya, Takahiro; Tsuchida, Yumi; Okamura, Tomohisa; Fujio, Keishi (Frontiers in Immunology, 2025)
ObjectiveTo explore the relationship between physique and immunological disturbances in systemic lupus erythematosus (SLE), we analyzed the clinical, immunological and transcriptomic characteristics of patients with SLE in relation to body mass index (BMI).MethodsClinical characteristics were obtained from patient charts, and serum cytokine levels were measured. Phenotypes and transcriptomes of peripheral immune cells from patients with SLE in the ImmuNexUT database were analyzed in relation to BMI.ResultsThirty-four SLE patients were included in the analysis. Fever and mucocutaneous symptoms were commonly observed in SLE patients with a low BMI. BMI was negatively correlated with the SLE disease activity (SLEDAI)-2K scores. Multiple regression analysis revealed that BMI was an independent explanatory variable for SLEDAI-2K scores, irrespective of anti-dsDNA antibody or complement levels. Although serum interferon (IFN)-alpha and IFN-gamma levels were negatively associated with BMI, causal mediation analysis showed that BMI had a direct effect on SLEDAI-2K scores, independent of IFN-alpha levels. Immunophenotyping indicated that BMI was primarily correlated with T cell subsets. BMI-related gene expression was mainly enriched in the regulatory T cells and B cell subsets. BMI was negatively correlated with several cellular metabolic pathways, including glucose metabolism-related pathways in Th1 and effector memory CD8+ T cells, but not with IFN signaling.ConclusionWe characterized the clinical, immunological and transcriptomic profiles of SLE patients with varying BMI. As low BMI was identified as an independent parameter for explaining disease activity, cachexia is considered one of the systemic symptoms of active SLE. Additionally, BMI influenced the phenotypic and transcriptomic alterations of acquired immune cells, independent of IFN signaling. These findings provide insights into the pathogenesis of SLE.